Current and Emerging Pharmacotherapy for Fibromyalgia - Roie Tzadok; Jacob N. Ablin (Pain Research and Management)
Introduction. Fibromyalgia syndrome (FMS) is a pain disorder with an estimated prevalence of 1–5%. It is associated with a variety of somatic and psychological disorders. Its exact pathogenesis is still unclear but is involved with neural oversensitization and decreased conditioned pain modulation (CPM), combined with cognitive dysfunction, memory impairment, and altered information processing. Connectivity between brain areas involved in pain processing, alertness, and cognition is increased in the syndrome, making its pharmacologic therapy complex. Only three drugs, pregabalin, duloxetine, and milnacipran are currently FDA-approved for FM treatment, but many other agents have been tested over the years, with varying efficacy. Areas Covered. The purpose of this review is to summarize current clinical experience with different pharmacologic treatments used for fibromyalgia and introduce future perspectives in developing therapies. Expert Opinion. Future insights into the fields of cannabinoid and opioid research, as well as an integrative approach towards the incorporation of genetics and functional imaging combined with additional fields of research relevant towards the study of complex CNS disorders, are likely to lead to new developments of novel tailor-made treatments for FMS patients.